APROKSIMASI DISTRIBUSI WAKTU HIDUP YANG AKAN DATANG - Pentury, Thomas; Matakupan, Rudy W.; Sinay, Lexy J. (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2011)
This paper give an analitical technique to approximate future lifetime distributions. Approximations of the future lifetime distribution based on the shifted Jacobi polynomials, andit yielded the sequences of a exponentials combination. The results of approximations of the future lifetime distribution in this cases study based on Makeham’s Law. It is very accurate inthe case study.